2007
DOI: 10.2214/ajr.05.2131
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Pulmonary Nodules: Detection, Characterization, and Guidance for Further Diagnostic Workup and Treatment

Abstract: Information on the morphologic and hemodynamic characteristics of SPNs provided by dynamic helical CT, with high specificity and reasonably high accuracy, can be used for initial assessment. PET/CT is more sensitive at detecting malignancy than dynamic helical CT, and all malignant nodules may be potentially diagnosed as malignant by both techniques. Therefore, PET/CT may be selectively performed to characterize SPNs that show indeterminate results at dynamic helical CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 77 publications
2
76
0
10
Order By: Relevance
“…Generally speaking, typical noncalcified nodules refer to solid lesions with diameters ranging from 8 to 30 mm [26,27]. Malignant probability for the smaller ones are usually low, especially for those less than 5 mm, only about 0-1 % [27][28][29]. Accordingly, we overlooked nodules with a maximum diameter below 5 mm; but larger ones over 30 mm were considered to be positive.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, typical noncalcified nodules refer to solid lesions with diameters ranging from 8 to 30 mm [26,27]. Malignant probability for the smaller ones are usually low, especially for those less than 5 mm, only about 0-1 % [27][28][29]. Accordingly, we overlooked nodules with a maximum diameter below 5 mm; but larger ones over 30 mm were considered to be positive.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of SPN is a challenging and important issue, since from 2-13 % in screening studies up to 46-82 % in PET/CT studies can be malignant [3,9,10]. The current gold standard is pathology, unfeasible in many cases and carrying risks [10] difficult to be justified in subjects with a low probability of cancer.…”
Section: Diagnostic Imaging In Spnmentioning
confidence: 99%
“…Small solitary pulmonary nodules are likely to be benign. A screening study by Henschke et al in 2004 found that none of the detected malignancies were less than 5 mm in diameter [10] The prevalence of malignancy correlates with nodule size (0% -1% for nodules/5 mm, 6% -28% for nodules 5 -10 mm, 33% -60% for nodules 11 -20 mm, and 64% -82% for nodules greater than 20 mm) [9] [13].…”
Section: Sizementioning
confidence: 99%
“…Depending on the appearance and radiologic context, certain SPNs are judged sufficiently typical of benign masses that follow-up is not warranted. Important factors that suggest benignity is the presence of characteristic calcification, the presence of fat with the SPN, the size, rate of growth certain characteristics such as SPN margins [10].…”
Section: Introductionmentioning
confidence: 99%